2022
DOI: 10.1017/dsj.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

A framework for ‘configuring participation’ in living labs

Abstract: In recent years, ‘living lab (LL)’, a design approach that actively involves users as partners from the early stage of the design process, has been attracting much attention. Compared with the traditional participatory design or co-design approaches, one of the distinctive features of the LL approach is that the process of and opportunity for user participation tends to be long-term and complex. Thus, LL practitioners must appropriately plan and design effective integration of user participation into the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…53 Yasuoka et al 54 showed it as a cyclical process entailing idea creation, prototyping and user testing. Akasaka et al 55 further highlighted three features of the living lab method, including "testing in a real-life environment or a similar environment," "involving users from the early to late stages of the process" and a "long-term design process. "…”
Section: Living Labsmentioning
confidence: 99%
“…53 Yasuoka et al 54 showed it as a cyclical process entailing idea creation, prototyping and user testing. Akasaka et al 55 further highlighted three features of the living lab method, including "testing in a real-life environment or a similar environment," "involving users from the early to late stages of the process" and a "long-term design process. "…”
Section: Living Labsmentioning
confidence: 99%
“…In recent years, European states and cities have particularly focused on the application of participative approaches, such as Living Labs [16,17], rather than traditional methods; this type of new concept allows policymakers to have an optimal view of the entire process from preparation to implementation and monitoring, by tailoring the participation of users during each step of the process [18]. This novel approach enables strategies to be formulated with an emphasis on attainable objectives, such as (a) economic benefits, (b) non-economic benefits, (c) stimulating participation and promoting partnerships, or a combination of the two.…”
Section: Participative Approaches For More Accessible Citiesmentioning
confidence: 99%
“…One of the projects is a four-month-long co-creation program with citizens to create a future vision of living environments for seniors (Akasaka, Mitake, Watanabe & Kawasaki, 2023). In collaboration with the town management organization, this program led 17 citizen participants of different ages (20s-70s) in designing imaginary living environments and services for themselves based on their experience and the knowledge obtained regarding senior lives and future technologies.…”
Section: : Co-creation In Projectsmentioning
confidence: 99%